2012
DOI: 10.1038/bjc.2012.290
|View full text |Cite
|
Sign up to set email alerts
|

A replicated association between polymorphisms near TNFα and risk for adverse reactions to radiotherapy

Abstract: Background: Response to radiotherapy varies between individuals both in terms of efficacy and adverse reactions. Finding genetic determinants of radiation response would allow the tailoring of the treatment, either by altering the radiation dose or by surgery. Despite a growing number of studies in radiogenomics, there are no well-replicated genetic association results. Methods: We carried out a candidate gene association study and replicated the result using three addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 26 publications
0
37
1
Order By: Relevance
“…One of these SNPs (rs2236599), resulting in a G to A change, was identified in 31 of 52 patients with ESCC (0.596), an allele frequency much higher than in the general population (0.140) 24 ; of note, allelic frequency for this SNP is particularly high in East Asians (0.293), in whom ESCC incidence is elevated. 2 The KLF4 rs2236599 SNP has been associated with radiotherapy toxicity during breast cancer treatment, 25 suggesting that this SNP may have functional consequences. We next investigated whether KLF4 is silenced epigenetically in human ESCC.…”
Section: Resultsmentioning
confidence: 99%
“…One of these SNPs (rs2236599), resulting in a G to A change, was identified in 31 of 52 patients with ESCC (0.596), an allele frequency much higher than in the general population (0.140) 24 ; of note, allelic frequency for this SNP is particularly high in East Asians (0.293), in whom ESCC incidence is elevated. 2 The KLF4 rs2236599 SNP has been associated with radiotherapy toxicity during breast cancer treatment, 25 suggesting that this SNP may have functional consequences. We next investigated whether KLF4 is silenced epigenetically in human ESCC.…”
Section: Resultsmentioning
confidence: 99%
“…Two large cohort studies focusing on radiation-induced toxicities developed in breast and prostate cancers were recently published (26,28). One study by Barnett et al (26), involving 1,613 breast and prostate cancer patients, captured common variants using tag SNPs with MAF<0.05 and functional SNPs in 92 genes and found no association in any of the SNPs.…”
Section: Most Significant Omnibus Test ------------------------------mentioning
confidence: 99%
“…One study by Barnett et al (26), involving 1,613 breast and prostate cancer patients, captured common variants using tag SNPs with MAF<0.05 and functional SNPs in 92 genes and found no association in any of the SNPs. Furthermore, a replication study by Talbot et al (28), involving 2,036 patients from three cohorts, captured 43 candidate SNPs in 35 genes and found that TNF-α may be associated with increased risk of radiation toxicities in breast cancer patients. No previously reported associations were found to be significant in those studies.…”
Section: Most Significant Omnibus Test ------------------------------mentioning
confidence: 99%
“…The studies tested many SNPs without adjusting for multiple comparisons and, although many reported positive associations, findings have proved difficult to replicate. One exception is a candidate gene study of 2036 women whose toxicity was scored after radiotherapy for breast cancer, which included a validation cohort to confirm the findings, and suggested a link between variation near the tumour necrosis factor alpha (TNF-a) gene and toxicity [60].…”
Section: Candidate Gene Studiesmentioning
confidence: 99%